Nutritional Awareness Level and its Impact on Sports Activity from the Viewpoint of the Department of Physical and Health Education Students at Al-Ahliyya Amman University - Alkasasbeh, Walaa Jumah; Mobaideen, Mohammed Ahmad; Hammad, Saleh Mahmoud (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to identify the level of nutritional awareness and its impact on sports activity from the viewpoint of students of the Department of Physical and Health Education at Al-Ahliyya Amman University. Methods: The researchers used the descriptive method and questionnaire to collect data. The study sample consisted of 132 male and female students from the department of Physical and Health Education at Al-Ahliyya Amman University, and this sample represented 88.6% of the study community, which totaled 150 students. The study used arithmetic averages, standard deviations, percentages, T-tests, Cronbach's alpha equation, and regression coefficient analysis. Using Analysis of Variance and the F-test to analyze the results of the study. Results: the results showed a high level of nutritional awareness among students, and also confirmed a statistically significant relationship between the level of nutritional awareness and the practice of sports activity، the level of nutritional awareness and its effect on sports activity varied in the variables of sex, school year, age and weight. Conclusions: The study recommended the need of increasing courses related to nutrition for athletes to increase awareness of the importance of nutrition among specialists in this field.